1984
DOI: 10.1002/em.2860060407
|View full text |Cite
|
Sign up to set email alerts
|

Use of aroclor 1254‐induced rat liver homogenate in the assaying of promutagens in chinese hamster ovary cells

Abstract: Seven promutagens belonging to two chemical classes--polycyclic aromatic hydrocarbons (PAHs) (benzo[a]pyrene, dimethyl benz[a]anthracene, 3-methylcholanthrene, fluoranthene) and alkyl nitrosamines (dimethyl, diethyl, and dibutyl nitrosamine)--were studied in Chinese hamster ovary (CHO) cells. Findings of practical importance in the use of Aroclor 1254-induced rat liver homogenate (S9) in the CHO/hypoxanthine-guanine phosphoribosyl transferase (HGPRT) mutation assay were made. Our novel findings are (1) the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…We found that the different S9s caused declines in RS in the absence of chemical treatment, with ethanol‐induced S9 having the greatest effect. All S9s, even at low concentrations, impaired cell survival; this is consistent with published work (e.g., [Li, ]). Although none of the S9s caused MN induction on their own, they differed in their ability to bioactivate chemicals to induce MN as expected.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the different S9s caused declines in RS in the absence of chemical treatment, with ethanol‐induced S9 having the greatest effect. All S9s, even at low concentrations, impaired cell survival; this is consistent with published work (e.g., [Li, ]). Although none of the S9s caused MN induction on their own, they differed in their ability to bioactivate chemicals to induce MN as expected.…”
Section: Discussionsupporting
confidence: 93%
“…The GreenScreen HC +S9 protocol uses flow cytometry to overcome the fluorescent and light-absorbing properties of S9 extract, but the BlueScreen HC +S9 protocol allows in-plate detection by including wash steps after exposure to test compound and S9. Cytotoxicity of S9 extract limits cell exposure to about 3 h, 27 and the shorter incubation time means that higher concentrations of some genotoxins are required to activate GADD45a in reduced exposure duration +S9 protocols. For example, NQO has an MEC of 0.06 µg/mL in GreenScreen HC -S9 (48 h) but 1 µg/mL in GreenScreen HC +S9 (3 h).…”
Section: Discussionmentioning
confidence: 99%
“…Published on November 8, 2021as DOI: 10.1124 at ASPET Journals on November 14, 2021 dmd.aspetjournals.org Downloaded from concentrations due to leakage, drug metabolism by MMHH requires cofactor supplementation and thereby can be directed via cofactor specification, for instance, reduced nicotinamide adenine dinucleotide phosphate (NADPH) for phase 1 oxidation, uridine 5′-diphosphoglucuronic acid (UDPGA) for uridine 5'-diphospho-glucuronosyltransferase (UDP-glucuronosyltransferase, UGT) mediated glucuronidation, 3'-phosphoadenosine 5'-phosphosulfate (PAPS) for cytosolic sulfotransferase (SULT)mediated sulfate conjugation, and reduced glutathione (GSH) for glutathione S-transferase (GST)mediated GSH conjugation). These features suggest that MMHH may also be applicable as an exogenous activating system for protoxicant activation for a co-cultured target cells, akin to the application of induced rat liver S9 in the evaluation of promutagens in genotoxicity assays (McCann et al, 1975;Li, 1984;Mitchell et al, 1997). Furthermore, the contribution of specific drug metabolism pathways towards drug toxicity may be defined via supplementation of MMHH with selected cofactors.…”
Section: Introductionmentioning
confidence: 99%